Multibeam bathymetry processed data (Atlas Hydrosweep DS 2 echo sounder entire dataset) of RV POLARSTERN during cruise ANT-XVIII/5a (PS58), Southern Ocean, South Pacific Ocean - Schenke, Hans Werner; Gauger, Steffen; Jacops, Merijn J; Krocker, Ralf; Dreutter, Simon; Dorschel, Boris (PANGAEA, 2025)
Multibeam data were collected during RV Polarstern cruise ANT-XVIII/5a (2001-02-24 to 2001-04-12). Multibeam sonar system was Atlas Hydrographic Hydrosweep DS 2 multibeam echo sounder. Data are processed with Caris HIPS, including sound velocity correction by cross fan calibration, tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.
Keywords: Bathymetry; Hydrosweep DS2; Multibeam; Polarstern; Southern Ocean; South Pacific Ocean